Implementation of Building Information Modelling (BIM) for the Operation and Maintenance (O&M) Phase of the Building Life Cycle in Malaysia - Chin Keng, Tan; Fadhaililamal, Fierra Hailly (Journal of Technology Management and Business, 2025)
Facilities Management (FM) plays a pivotal role in the operation and maintenance (O&M) phase of a building’s life cycle. Despite various data management systems available for building maintenance, manual processes that deal with scattered and unformatted data still dominate. Building Information Modelling (BIM), a digital method introduced in the construction sector, has demonstrated its potential to enhance efficiency throughout a building’s life cycle. However, its full potential in revolutionizing facilities management during the O&M phase remains largely unexplored and minimally implemented in Malaysia. This study has three objectives: to examine the implementation of BIM for the O&M phase, identify barriers to the implementation, and propose strategies to improve its implementation. Data was collected through questionnaires. The findings reveal that BIM adoption is in its early stages, with limited projects related to BIM. Critical barriers to implement BIM include the high-cost investment, lack of technical expertise, complex facility information, lack of preparation of materials and equipment by academic institutions, and unclear workflows within organisations. The study recommends key strategies such as comprehensive training, BIM education to reduce technical issues related to files and systems, secured funding, collaboration among FM stakeholders, and clearly defined objectives. These findings highlight the barriers the current FM practice faces and provide a roadmap for implementing BIM for the O&M phase of the building life cycle in Malaysia.